Effect of oxygen and hydrogen flow ratio on indium tin oxide films in rear-junction silicon heterojunction solar cells. (1st January 2022) - Qiu, Depeng; Duan, Weiyuan; Lambertz, Andreas; Bittkau, Karsten; Qiu, Kaifu; Rau, Uwe; Ding, Kaining
Highlights: An increase of the carrier density and mobility can be achieved by using hydrogen during the sputtering process, ascribed to the additional H dopants in the films and passivation in the grain boundary. Compared with reducing the oxygen gas flow, putting small amount of hydrogen into the sputtering mixture gases could be a better strategy to balance the electrical and optical properties of the ITO layers. A degradation of both field-effect and chemical passivation quality was obtained for experimental devices with hydrogenated ITO, attributed to the etching effect of H on a-Si:H(n) and more effusion of H from a-Si:H(i) layer into ITO layers. A significant improvement of FF (∼1.1 %abs ) with sacrifice of J sc (∼0.3 mA/cm 2 ) were obtained at 2% of f H2 and 0.8 Pa of pressure, yielding 0.18 %abs gain of efficiency. The best solar cell with hydrogenated ITO exhibits η of 22.97%, V oc of 735 mV, FF of 82.15% and J sc of 38.03 mA/cm 2 . Abstract: The influence of the oxygen flow ratio ( f O2 ) and hydrogen flow ratio ( f H2 ) on the optoelectronic properties of the indium tin oxide (ITO) films are studied together. An increase of the carrier density and mobility can be achieved by using hydrogen during the sputtering process, resulting in an improvement of the film conductivity. Compared with reducing the oxygen gas flow, putting small amount of hydrogen into the sputtering mixture gases could be a better strategy to balance the electrical and optical properties of the ITO layers. Quokka3 simulation demonstrates 0.1 %abs improvement of power conversion efficiency ( η ) at 2% of f H2 compared to reference based on the ITO material properties. Full-size M2 solar cells with various ITO layers were fabricated. A degradation of passivation quality for the devices with hydrogenated ITO (ITO:H) was observed after sputtering process, ascribed to the etching effect of hydrogen radicals on the amorphous silicon (a-Si:H) layer and the extraction of hydrogen from a-Si:H (i) to ITO layers. It is proved that this sputter damage can be eliminated by increasing the pressure of ITO:H above 0.5 Pa. Finally, a ∼ 0.18% gain of η was obtained at f H2 of 2% and pressure of 0.8 Pa and the best cell shows the η of 22.97%, V oc of 735 mV, FF of 82.15% and J sc of 38.03 mA/cm 2 .